2009
DOI: 10.1152/ajpgi.90685.2008
|View full text |Cite
|
Sign up to set email alerts
|

Role of serotonin in intestinal inflammation: knockout of serotonin reuptake transporter exacerbates 2,4,6-trinitrobenzene sulfonic acid colitis in mice

Abstract: Serotonin (5-HT) regulates peristaltic and secretory reflexes in the gut. The serotonin reuptake transporter (SERT; SLC6A4), which inactivates 5-HT, is expressed in the intestinal mucosa and the enteric nervous system. Stool water content is increased and colonic motility is irregular in mice with a targeted deletion of SERT. We tested the hypotheses that 5-HT plays a role in regulating intestinal inflammation and that the potentiation of serotonergic signaling that results from SERT deletion is proinflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
144
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(158 citation statements)
references
References 60 publications
13
144
1
Order By: Relevance
“…Small intestinal motility was measured as described previously. 17 Briefly, all animals received an intragastric bolus dose of a charcoal solution (charcoal 0.5 g, arabigum 0.25 g and NaCl (0.9%) 5 ml) by gavage 10 min before euthanization. Five minutes later, the animals were anesthetized with 80 mg ketamine and 6 mg xylazine per kg body weight intraperitoneally.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small intestinal motility was measured as described previously. 17 Briefly, all animals received an intragastric bolus dose of a charcoal solution (charcoal 0.5 g, arabigum 0.25 g and NaCl (0.9%) 5 ml) by gavage 10 min before euthanization. Five minutes later, the animals were anesthetized with 80 mg ketamine and 6 mg xylazine per kg body weight intraperitoneally.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…The numbers of 5-HT-positive cells in the small intestine were counted in 10 randomly selected fields using a Zeiss microscope (Axio Vert 200M) (Zeiss, Jena, Germany) with the magnification of  400. 17 b-Hydroxybutyrate concentration in plasma b-Hydroxybutyrate was measured in the plasma using a commercially available kit according to the manufacture's instructions (Randox).…”
Section: Immunohistochemical Staining Of Serotoninmentioning
confidence: 99%
“…Recently, we have shown that TPH1-deficient (TPH1 2/2 ) mice, which have significantly lower amounts of 5-HT in the gut, exhibit reduced severity of colitis in two different models of experimental colitis (induced by dextran sulfate sodium [DSS] and dinitrobenzene sulfonic acid [DNBS]), whereas replenishing 5-HT levels upregulated colitis severity (24). A proinflammatory role for 5-HT has also been demonstrated in other studies where chemicalinduced colitis or spontaneous colitis associated with an IL-10 deficiency is increased in severity when coupled with the 5-HTenhancing effects of a knockout of the serotonin reuptake transporter, SERT (25,26). We have also shown that 5-HT plays a key role in the activation of immune cells to produce proinflammatory cytokines (24,27).…”
mentioning
confidence: 98%
“…But the results of AWR tests and EMG recordings showed that no differences were found in visceral pain threshold pressure between the rats that were treated with pCPA and the rats in the control group. This result indicated that even below the normal level of 5-HT content may be enough to meet the minimum requirement of invoking the sensory reflex (21)(22)(23).…”
Section: Discussionmentioning
confidence: 90%